1998
DOI: 10.1111/j.1939-1676.1998.tb02107.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Channel Blockers in Veterinary Medicine

Abstract: Calcium channel blockers are becoming increasingly popular in veterinary medicine for the treatment of systemic hypertension, cardiac arrhythmias, and hypertrophic cardiomyopathy. Calcium is vital to many cellular functions and thus stringent regulation of intracellular calcium concentrations is required. Pharmacologic manipulation of the regulatory mechanisms has the potential to alter cellular function in all body systems. In human medicine, calcium channel blockers are being evaluated for, among other thing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
31
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 47 publications
(3 reference statements)
3
31
0
1
Order By: Relevance
“…Amlodipine is a dihydropyridine calcium channel blocker (CCB) with direct peripheral vasodilatory effects and weaker central negative chronotropic and inotropic effects (Stopher and others 1988, Cooke and Snyder 1998, Atkins and others 2007). It is considered the treatment of choice for the management of SHT in cats with CKD (Henik and others 1997, Snyder 1998, Maggio and others 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Amlodipine is a dihydropyridine calcium channel blocker (CCB) with direct peripheral vasodilatory effects and weaker central negative chronotropic and inotropic effects (Stopher and others 1988, Cooke and Snyder 1998, Atkins and others 2007). It is considered the treatment of choice for the management of SHT in cats with CKD (Henik and others 1997, Snyder 1998, Maggio and others 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Amlodipine is a second‐generation dihydropyridine and exerts its effects by blocking L‐type calcium channels in vascular smooth muscle. It binds and dissociates from its receptor fairly slowly, which accounts for the gradual onset and slow waning of effect . This, in combination with its long plasma half‐life, means amlodipine only needs to be administered once every 24 hours .…”
mentioning
confidence: 99%
“…It is a very widely used calcium channel blocker in arterial hypertension therapy. It has a longer elimination half-life than other dihydropyridines (30 hours in the dog), suffering less variation in plasma concentration during chronic administration [1]. In anaesthetized Beagle dogs, it has been demonstrated that amlodipine increased blood flow within the ocular circulation [5].…”
Section: Introductionmentioning
confidence: 98%
“…Calcium enters excitable cells through different types of voltage-gated calcium channels. Among them, the L-type is the predominant calcium channel in skeletal, cardiac and vascular smooth muscle [1]. Drugs Luís Silva-Carvalho-in memoriam This work was supported by CIISA (Centro de Investigação Interdisciplinar em Sanidade Animal).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation